A Novel Enterovirus 71 (EV71) Virulence Determinant: The 69th Residue of 3C Protease Modulates Pathogenicity - Li, Bingqing; Yue, Yingying; Zhang, Yajie; Yuan, Zenglin; Li, Peng; Song, Nannan; Lin, Wei; Liu, Yan; Gu, Lichuan; Meng, Hong (Frontiers in Cellular and Infection Microbiology, 2017)
Human enterovirus type 71 (EV71), the major causative agent of hand-foot-and-mouth disease, has been known to cause fatal neurological complications. Unfortunately, the reason for neurological complications that have been seen in fatal cases of the disease and the relationship between EV71 virulence and viral genetic sequences remains largely undefined. The 3C protease (3Cpro) of EV71 plays an irreplaceable role in segmenting the precursor polyprotein during viral replication, and intervening with host life activity during viral infection. In this study, for the first time, the 69th residue of 3C protease has been identified as a novel virulence determinant of EV71. The recombinant virus with single point variation, in the 69th of 3Cpro, exhibited obvious decline in replication, and virulence. We further determined the crystal structure of 3C N69D at 1.39 Ǻ resolution and found that conformation of 3C N69D demonstrated significant changes compared with a normal 3C protein, in the substrate-binding site and catalytic active site. Strikingly, one of the switch loops, essential in fixing substrates, adopts an open conformation in the 3C N69D-rupintrivir complex. Consistent with this apparent structural disruption, the catalytic activity of 3C N69D decreased sharply for host derived and viral derived substrates, detected for both in vitro and in vivo. Interestingly, in addition to EV71, Asp69 was also found in 3C proteases of other virus strains, such as CAV16, and was conserved in nearly all C type human rhinovirus. Overall, we identified a natural virulence determinant of 3C protease and revealed the mechanism of attenuated virulence is mediated by N69D substitution. Our data provides new insight into the enzymatic mechanism of a subdued 3C protease and suggests a theoretical basis for virulence determinantion of picornaviridae.